Clinico-Epidemiological Pattern of Penile Emergency in a Nigerian Hospital - Idowu , Najeem Adedamola; Odeyemi, Peter Olalekan; Ajekwu, Samuel C; Adeleye-Idowu, Suliyat Adebisi; Ajala, Samson Adeshina; Saliu, Abdulrasheed O; Adedokun, Stephen Ishola (The Thai Journal of Surgery, 2025)
Objective: Acute penile condition is a relatively uncommon urological emergency. This condition may lead to penile organ dysfunction if intervention is delayed. The commonly seen penile emergencies are priapism, penile fracture, and traumatic penile injury, among others. Our objective was to review all cases of penile emergencies managed over a period of four years (2020-2024) at our center. Patients and Methods: This was a retrospective review of all cases managed for penile emergencies over a period of two years. The case files of the patients were retrieved from the hospital record department. The information extracted was written in a designed proforma. A descriptive statistic was carried out on the data. Results: A total number of 19 cases of penile emergencies were managed during the years under review. The age range of the study group was 0.08-46 years, with a median of 23.9 ± 11.44 SD. The median duration of symptoms at presentation was 64.4 ± 123.2 SD with a range of 2 hours -504 hours. About half of the cases were traumatic (10 patients, 52.6%). The review of the underlined etiology showed sickle cell anemia, coital trauma, self-inflicted genital mutilation, circumcision injury, blunt penile trauma, and Fournier gangrene. Twelve patients (63.2%) had surgical intervention, while the rest were managed non-operatively. Post-intervention evaluation of erectile function done in three priapic patients with partners showed severe erectile dysfunction. Conclusion: The most common (nontraumatic) penile emergency from this series was low-flow priapism. The majority of them had successful nonoperative measures with diluted adrenaline. Adrenaline may be an alternative sympathomimetic drug to the more preferred phenylephrine when not available. Other acute penile conditions noted were penile fracture and penile amputation, some of which had successful emergency interventions.